Personalized hip joint kinetics during deep squatting in young, athletic adults. Issue 1 (2nd January 2020) - Van Houcke, Jan; Galibarov, Pavel E.; Van Acker, Gilles; Fauconnier, Sigrid; Allaert, Ellen; Van Hoof, Tom; Almeida, Diogo F.; Steenackers, Gunther; Pattyn, Christophe; Audenaert, Emmanuel A.
Abstract: The goal of this study was to report deep squat hip kinetics in young, athletic adults using a personalized numerical model solution based on inverse dynamics. Thirty-five healthy subjects underwent deep squat motion capture acquisitions and MRI scans of the lower extremities. Musculoskeletal models were personalized using each subject's lower limb anatomy. The average peak hip joint reaction force was 274 percent bodyweight. Average peak hip and knee flexion angles were 107° and 112° respectively. These new findings show that deep squatting kinetics in the younger population differ substantially from the previously reported in vivo data in older subjects.